Utilization of Health Care and Burden of Out-of-Pocket Health Expenditure in Zimbabwe: Results from a National Household Survey. Issue 4 (2nd October 2018) - Zeng, Wu; Lannes, Laurence; Mutasa, Ronald
Abstract: In the last decade, Zimbabwe has undertaken substantial changes and implemented new initiatives to improve health system performance and services delivery, including results-based financing in rural health facilities. This study aims to examine the utilization of health services and level of financial risk protection of Zimbabwe's health system. Using a multistage sampling approach, 7, 135 households with a total of 32, 294 individuals were surveyed in early 2016 on utilization of health services, out-of-pocket (OOP) health expenditure, and household consumption (as a measure of living standards) in 2015. The study found that the outpatient visits were favorable to the poor but the poorest had less access to inpatient care. In 2015, household OOP expenditure accounted for about one quarter of total health expenditure in Zimbabwe and 7.6% of households incurred catastrophic health expenditure (CHE). The incidence of CHE was 13.4% in the poorest quintile in comparison with 2.8% in the richest. Additionally, 1.29% of households fell into poverty due to health care–related expenditures. The study suggests that there are inequalities in utilization of health services among different population groups. The poor seeking inpatient care are the most vulnerable to CHE.